Ireland : 6000 B. C. -1972 : a chronology and fact book - Griffin, William D. (N.Y. : Oceana Publications, 1973)
A chronology of Irish history, emphasizing its modern political events and containing pertinent documents and statistics.
Bibliography : p. 145-152.
Keywords: Ireland -- History -- Sources; Ireland -- History -- Chronology